Factors prospectively associated with physical activity and dietary related outcomes in people with severe mental illness: A systematic review of longitudinal studies. (March 2019) - Hassan, Suzan; Ross, Jamie; Marston, Louise; Osborn, David; Walters, Kate
Highlights: There is a paucity of high-quality longitudinal studies in this area. Further research is needed to uncover predictors of healthy physical activity/ diet uptake in SMI. Older age predicted better physical activity-related outcomes. Higher negative symptoms predicted poorer physical activity-related outcomes. PA intentions were unrelated to physical activity-related outcomes. Abstract: Understanding factors that contribute towards physical activity and diet outcomes are important for health improvement in people with severe mental illness. Cross-sectional findings on factors associated with diet and physical activity outcomes provide limited information on what predicts changes or long-term outcomes in lifestyle behaviours in people with severe mental illness. A systematic review was therefore conducted to identify prospective studies with quantitative data on baseline factors associated with follow-up diet or physical activity related outcomes. MEDLINE, EMBASE, PsycINFO, CINAHL Plus and grey literature databases were searched from inception to March 2018. From 6921 studies, 5 were eligible for physical activity related outcomes and 2 for diet related outcomes. The follow-up duration was 4 weeks to 24 months and participants were mostly diagnosed with schizophrenia. Older age was commonly related to better physical activity related outcomes, whilst higher negative symptoms were related to poorer-related outcomes. Physical activity intentions and gender were unrelated to physical activity outcomes. There was a lack of data on factors influencing dietary outcomes. Although there were some common factors predictive of physical activity including older age and negative symptoms, more high-quality research is needed to determine the effect of sociodemographic, mental health, social, clinical, lifestyle and other factors on both physical activity and dietary outcomes.